Enhancing RMG Supply Chain Efficiency through Automation: A Path to Cost Reduction in Bangladeshs Garment Industry (Global Journal of Management and Business Research, 2023)
Bangladesh s RMG sector is the cornerstone of nation s economy and currently grappling with rising cost due to transportation inefficiencies within the supply chain This study delves into the escalating product prices attributed to the transportation cost and highlighted the role of transport and logistics operations Analyzing data from RMG Companies this study unveils the impact of transportation in product pricing and identifies various challenges contributing to the problem at hand The research emphasizes the need for automation and Industry 4 0 RMG logistics operation www fibre2fashion com 22 and explores the hurdles faced by emerging economy in adopting 21st century technologies The aim of this study is to envision cost efficient supply chain and enhance global competition readiness of the RMG sector of Bangladesh
Keywords: transportation; RMG sector; supply chain analysis; logistics optimization; supply chain efficiency; industry 40 in logistics; logistics efficiency